A Comparison between the Results of Open versus Closed Lateral Internal Sphincterotomy in the Surgical Management of Chronic Anal Fissure - Mahabub, Md; Rahman, Md Mahbubur; Islam, Md Tanvirul; Sultana, Selina (BIRDEM Medical Journal, 2018)
Background: Lateral internal sphincterotomy is regarded as the gold standard surgical treatment for chronic anal fissure. Some authors reported that the closed technique had lower complication rates than that by the open technique, but others reported that both of the techniques had no meaningful differences in complications. Methods: This was a comparative and cohort study carried out at Department of Colorectal Surgery, Combined Military Hospital (CMH) Dhaka, Bangladesh, from October 2013 to October 2017. Eighty three patients with chronic anal fissure not responding to medical treatment for at least three months were included in this study to compare the results of the open versus closed techniques of lateral internal sphincterotomy after four months follow up postoperatively. Results: The mean age at presentation was 34.15±11.4 years and the male to female ratio was 1.24:1. The results of open and closed techniques were compared regarding per-operative bleeding (35.71% versus 12.19%), post-operative urinary retention (4.76% versus 0%), symptom relief on first post-operative day (76.19% versus 70.73%), significant 1st post-operative day pain in the operated wound (33.33% versus 7.31%), temporary fecal soiling (2.38% versus 0%), temporary flatus incontinence (7.14% versus 0%), and fissure recurrence (0% versus 14.63%) respectively. Temporary incontinence to fecal and flatus recovered by conservative management within two and four months of surgery respectively. Conclusion: The closed technique of lateral internal sphincterotomy had lower post-operative complications, pain, bleeding, and incontinence compared to open technique, but increased risk of fissure recurrence. Birdem Med J 2018; 8(3): 235-239